The identification of factor/factor that influencing the level of motivation among employees in manufacturing sector of SME in Kuching - Chan, Kiang Kiong (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this research is to identify what factor/factors have relationship with the level of motivation among employees in manufacturing sector of SME Kuching. The factors included are salary/wage, incentive, recognition and working environment. The objectives of this research are to determine the relationship between the stated factors and the level of motivation among employees. A total number of 100 respondents from production department were being selected as sample for this research. As this is quantitative research, questionnaires were used as an instrument in this research. Demographic characteristics of respondents is analysed by descriptive statistic and reliability test and validity test will be run also. Hypotheses were measured using statistical analysis such as Pearson Correlation and Multiple Regression. The Pearson Correlation test is used to show a significant relationship between salary/wage, incentive, recognition and working environment and the level of motivation among employees. The implication of this research and limitation as well as recommendation for the future research is also discussed.